Pengaruh Kualitas Pelayanan Pendekatan Terra terhadap Kepuasan Pasien - Hamid, H. M.; Mulyani, S. R.; Wirawan, C. (Future Science, 2024)
The purpose of this research is to carry out a more explicit analysis regarding facilities and physical evidence, empathy, responsiveness, reliability, service guarantee, and patient satisfaction. The objects of this research were patients at Sariningsih Hospital in Bandung with a sample of 99 respondents. The data analysis used is multiple linear regression analysis, correlation coefficient analysis, and coefficient of determination analysis. Based on the multiple regression analysis equation model, the results show that there is a positive and unidirectional functional relationship between the variabels, which is Y = -1.596 + 0.388X1 + 0.440X2 + 0.338X3 + 0.103X4 + 0.353X5. It means that every change in the independent variabel can affect the dependent variabel as well. This is in line with the results of the correlation coefficient which shows a very strong relationship (0.944) and the coefficient of determination (89.1%) shows a large influence. Thus, to increase patient satisfaction, we firstly must pay attention to the quality of service.